SIRT1: Harnessing multiple pathways to hinder NAFLD - Cheng Tian; Rongrong Huang; Ming Xiang (Elsevier, 2024)
Non-alcoholic fatty liver disease (NAFLD) encompasses hepatic steatosis, non-alcoholic steatohepatitis (NASH), fibrosis, cirrhosis, and hepatocellular carcinoma. It is the primary cause of chronic liver disorders, with a high prevalence but no approved treatment. Therefore, it is indispensable to find a trustworthy therapy for NAFLD. Recently, mounting evidence illustrates that Sirtuin 1 (SIRT1) is strongly associated with NAFLD. SIRT1 activation or overexpression attenuate NAFLD, while SIRT1 deficiency aggravates NAFLD. Besides, an array of therapeutic agents, including natural compounds, synthetic compounds, traditional Chinese medicine formula, and stem cell transplantation, alleviates NALFD via SIRT1 activation or upregulation. Mechanically, SIRT1 alleviates NAFLD by reestablishing autophagy, enhancing mitochondrial function, suppressing oxidative stress, and coordinating lipid metabolism, as well as reducing hepatocyte apoptosis and inflammation. In this review, we introduced the structure and function of SIRT1 briefly, and summarized the effect of SIRT1 on NAFLD and its mechanism, along with the application of SIRT1 agonists in treating NAFLD.